2023
DOI: 10.1111/jcmm.18076
|View full text |Cite
|
Sign up to set email alerts
|

Loss of nephric augmenter of liver regeneration facilitates acute kidney injury via ACSL4‐mediated ferroptosis

Lili Huang,
Ling Zhang,
Zheng Zhang
et al.

Abstract: Ferroptosis, characterized by lipid accumulation in intracellular compartments, is related to acute kidney injury (AKI), but the mechanism remains obscure. In our previous study, the protective effect of augmenter of liver regeneration (ALR) on AKI was not fully clarified. In this study, we established an AKI mouse model by knocking out proximal tubule‐specific ALR and an AKI cell model by inducing hypoxia, as well as enrolled AKI patients, to investigate the effects of ALR on ferroptosis and the progression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…( 134 ) proposed that ferroptosis and programmed necrosis are complementary mechanisms of cell death. Within this framework, ACSL4, a key enzyme in lipid metabolism, was utilized as an indicator of ferroptosis, while mixed lineage kinase-like protein (MLKL), a protein involved in the execution of necrosis, served as a marker for programmed necrosis ( 135 , 136 ). These findings indicated that a deficiency in ACSL4 resulted in the upregulation of MLKL, which sensitized cells to ferroptosis ( 137 ).…”
Section: Ferroptosis and Other Forms Of Cell Deathmentioning
confidence: 99%
“…( 134 ) proposed that ferroptosis and programmed necrosis are complementary mechanisms of cell death. Within this framework, ACSL4, a key enzyme in lipid metabolism, was utilized as an indicator of ferroptosis, while mixed lineage kinase-like protein (MLKL), a protein involved in the execution of necrosis, served as a marker for programmed necrosis ( 135 , 136 ). These findings indicated that a deficiency in ACSL4 resulted in the upregulation of MLKL, which sensitized cells to ferroptosis ( 137 ).…”
Section: Ferroptosis and Other Forms Of Cell Deathmentioning
confidence: 99%